2024
DOI: 10.1021/acs.inorgchem.4c01218
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Inhibitory Mechanism of Aβ1–42 Aggregation by Diruthenium Complexes

Sara La Manna,
Valeria Panzetta,
Concetta Di Natale
et al.

Abstract: There is a growing interest in the search for metal-based therapeutics for protein misfolding disorders such as Alzheimer’s disease (AD). A novel and largely unexplored class of metallodrugs is constituted by paddlewheel diruthenium complexes, which exhibit unusual water solubility and stability and unique coordination modes to proteins. Here, we investigate the ability of the complexes [Ru2Cl(DPhF)(O2CCH3)3]·H2O (1), [Ru2Cl(DPhF)2(O2CCH3)2]·H2O (2), and K2[Ru2(DPhF)(CO3)3]·3H2O (3) (DPhF– = N,N′-diphenylforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…How these diruthenium compounds exert their antitumor activity is largely unknown, and only a few studies showed how they interact with biological molecules. Particularly, reactions with ascorbic acid or glutathione have been studied from a kinetic and mechanistic point of view, as well as the coordination to amino acids, proteins, nucleotides, or even RNA …”
Section: Introductionmentioning
confidence: 99%
“…How these diruthenium compounds exert their antitumor activity is largely unknown, and only a few studies showed how they interact with biological molecules. Particularly, reactions with ascorbic acid or glutathione have been studied from a kinetic and mechanistic point of view, as well as the coordination to amino acids, proteins, nucleotides, or even RNA …”
Section: Introductionmentioning
confidence: 99%